Atrybuty partycypacji pracowniczej w organizacji wirtualnej - Stankiewicz, Janina; Moczulska, Marta (Attribute of employee participation in virtual organization, 2006)
In the article the social aspects of virtual organization management arc presented. The attention is turned on the key workers' part of net functioning of co-operating organizations. There is a discussion about abilities needed to effective virtual cooperation. The meaning of independence in undertaking the decision from taking over the responsibility for it, consciousness of partners’ dissimilarity and the need of acceptance as well as suitable communicating is underlined. The activity of individual enterprises supporting the participation of its workers in virtual organization is shown, including the necessity of forming partnership relations between managers and subordinates with unique competences. The participation in aspect of specific running of virtual organization is presented. It is regarded as a favourable management method of creating desired for virtual cooperation workers' skills and forming essential atmosphere confidence.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1132, s. 197-204